Silmitasertib-induced macropinocytosis promoting DDP intracellular uptake to enhance cell apoptosis in oral squamous cell carcinoma - Shaojuan Song; Xin Xia; Jiajia Qi; Xiaopei Hu; Qian Chen; Jiang Liu; Ning Ji; Hang Zhao (Taylor & Francis Group, 2021)
Cisplatin (DDP) is a first-line chemotherapeutic drug applied for the treatment of oral squamous cell carcinoma (OSCC). The anticancer activity of DDP is tightly linked to its intracellular uptake. It is unwise to increase the DDP intake by increasing the dose or shortening the dosing interval because of the severe systemic toxicity (nephrotoxicity, ototoxicity and neurotoxicity) in DDP application. The main uptake pathways of DDP include passive diffusion and active transporter transport. Therefore, finding additional uptake pathways that can improve the effective intracellular concentration of DDP is critical. Macropinocytosis, an endocytic mechanism for extracellular material absorption, contributes to the intracellular uptake of anticancer drugs. No research has been conducted to determine whether macropinocytosis can augment the intracellular uptake of DDP in OSCC cells or not. Based on that, we proved for the first time that silmitasertib (previously CX-4945) could trigger macropinocytosis, which may increase the intracellular uptake of DDP and enhance apoptosis via in vivo and in vitro experiments. We hope that our findings will inspire a new approach for the application of DDP in cancer treatment.